Financial regulatory structure and the resolution of conflicting goals - Larry D. Wall; Robert A. Eisenbeis (Federal Reserve Bank of Atlanta, 1999)
The debate over modernizing the financial structure is raising questions about the merits of modernizing the financial regulatory structure. Regulatory structure is important because an almost unavoidable feature of our current system of government is that Congress assigns multiple goals that sometimes have conflicting policy implications to the regulatory agencies. The structure of the agencies is important to the resolution of these conflicts. Responsibility for two or more goals that have conflicting implications may be assigned to a single agency that is likely to resolve the conflict with a consistent set of policies based on the agency's priorities. Alternatively, the goals may be assigned to more than one agency, an action that often results in the conflicts being debated in the public arena but that may also result in the agencies' implementing inconsistent policies. This paper uses the problem of goal conflicts to provide a framework for evaluating alternative regulatory structures.
Keywords: 330; Banks and banking; Banking structure